Long-term forecasting of monthly mean reference evapotranspiration using deep neural network: A comparison of training strategies and approaches - Chia M.Y.; Huang Y.F.; Koo C.H.; Ng J.L.; Ahmed A.N.; El-Shafie A. (Elsevier Ltd, 2023)
Brain; Budget control; Convolution; Convolutional neural networks; Deep neural networks; Deterioration; Errors; Evapotranspiration; Forecasting; Mean square error; Multilayer neural networks; Convolutional neural network; Gated recurrent unit; Long-term forecasting; Memory network; Multiple inputs; Multiple outputs; Network models; Reference evapotranspiration; Time horizons; Training strategy; Long short-term memory